Brachial Plexus Birth Injuries: A Critical Analysis Review. Issue 6 (June 2021) - Pulos, Nicholas; Shaughnessy, William J.; Spinner, Robert J.; Shin, Alexander Y.
Abstract : The incidence of brachial plexus birth injury (BPBI) in the United States is declining and now occurs in <1 per 1, 000 births. The gold standard for predicting the need for early intervention remains serial examination. Early treatment of BPBI with reconstructive surgery requires the ability to perform both interposition nerve grafting and nerve transfers. Given the heterogeneity of lesions, the evidence is largely limited to retrospective comparative studies and case series.